Supporting Student Engagement with Technology: Findings from a Study of an Online Personal Learning Environment for Extensive Listening - Suppasetseree, Suksan; Kumdee, Soranut; Minh, Thang Ho (LEARN Journal: Language Education and Acquisition Research Network, 2023)
Learning English consists of four skills that students need to master: reading, writing, listening, and speaking. However, in EFL contexts, listening is found to be the most challenging and problematic skill for those students who encounter different kinds of listening problems. In order to improve Thai EFL students’ listening performance during the COVID-19 pandemic, a two-week research project was conducted both to measure the levels of student engagement and to explore their opinions towards an online Personal Learning Environment (PLE) focused on extensive listening activities. A mixed-methods research design was applied, which included a pre-questionnaire for the purpose of designing the online PLE platform and listening materials, and a post-questionnaire to measure student engagement. Additionally, a semi-structured interview was used to investigate students’ opinions towards the online PLE. The results showed high levels of student engagement in all three dimensions; behavioral, cognitive, and emotional. Students had positive opinions towards the online PLE because they found it enjoyable. Self-regulated and tailor-made learning also served to improve knowledge of vocabulary and pronunciation despite some personal problems with time management and internet connectivity during the project. These findings raise implications for educators, policymakers, and educational technology developers to consider when offering online PLEs for students’ self-regulated learning.